Nursing Informatics' Contribution to One Health - Peltonen Laura-Maria; O'Connor Siobhan; Conway Aaron; Cook Robyn; Currie Leanne M.; Goossen William; Hardiker Nicholas R.; Kinnunen Ulla-Mari; Ronquillo Charlene E.; Topaz Maxim; Rotegård Ann Kristin (Schattauer GmbH, 2025)
Objectives: To summarise contemporary knowledge in nursing informatics related to education, practice, governance and research in advancing One Health.
Methods: This descriptive study combined a theoretical and an empirical approach. Published literature on recent advancements and areas of interest in nursing informatics was explored. In addition, empirical data from International Medical Informatics Association (IMIA) Nursing Informatics (NI) society reports were extracted and categorised into key areas regarding needs, established activities, issues under development and items not current.
Results: A total of 1,772 references were identified through bibliographic database searches. After screening and assessment for eligibility, 146 articles were included in the review. Three topics were identified for each key area: 1) education: “building basic nursing informatics competence”, “interdisciplinary and interprofessional competence” and “supporting educators competence”; 2) practice: “digital nursing and patient care”, “evidence for timely issues in practice” and “patient-centred safe care”; 3) governance: “information systems in healthcare”, “standardised documentation in clinical context” and “concepts and interoperability”, and 4) research: “informatics literacy and competence”, “leadership and management”, and “electronic documentation of care”. 17 reports from society members were included. The data showed overlap with the literature, but also highlighted needs for further work, including more strategies, methods and competence in nursing informatics to support One Health.
Conclusions: Considering the results of this study, from the literature nursing informatics would appear to have a significant contribution to make to One Health across settings. Future work is needed for international guidelines on roles and policies as well as knowledge sharing.